Macroeconomic variables and in-migration in Malaysia’s developed states - Nor Ermawati Hussain,; Noor Haslina Mohamad Akhir,; Mohd Shahidan Shaari,; Diana Nabila Chau Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nowadays, in-migration is one of the important phenomena that affects urbanisation and development in the destination area. Indirectly, it will cause the rapid growth of the population, leads to overcrowding, competition for jobs, unemployment, poverty and the formation of new towns in the destination area especially urban areas. However, for rural destination areas, in-migration of professionals is important to stimulate economic growth. Hence, the objective of this study is to forecast and analyze the effect of macroeconomic variables on in-migration into developed states in Malaysia. Using the annual time series data from 1980 to 2012, Autoregression Distributed Lag (ARDL) and Grangercausality test were conducted. The findings have found that long run and short run relationships exist between inmigration and macroeconomic factors for developed states. The forecasting until year 2020 expects that in-migration will increase in Perak and Penang. Investment factors that are concentrated in the developed states also affect the population’s decision to migrate especially in Kuala Lumpur and Selangor. To promote the economic growth, foreign direct investment and domestic investment for development sector should be intensified to improve household incomes in the region. Besides, Perak and Selangor need to improve the existing policies to ensure that there is an increase in foreign direct investment and domestic investment.